A polypeptide coating for preventing biofilm on implants by inhibiting antibiotic resistance genes. (February 2023) - Liu, Danqing; Xi, Yuejing; Yu, Shunzhi; Yang, Kexin; Zhang, Fan; Yang, Yuying; Wang, Tianlong; He, Shisheng; Zhu, Yunqing; Fan, Zhen; Du, Jianzhong
Abstract: Aging population has been boosting the need for orthopedic implants. However, biofilm has been a major obstacle for orthopedic implants due to its insensitivity to antibiotics and tendency to drive antimicrobial resistance. Herein, an antibacterial polypeptide coating with excellent in vivo adhesive capacity was prepared to prevent implants from forming biofilms and inducing acquired antibiotic resistance. A peptide-based copolymer, poly[phenylalanine10 -stat- lysine12 ] -block -3, 4-dihydroxy-l -phenylalanine [Poly(Phe10 -stat- Lys12 )-DOPA] was modularly designed, where poly(Phe10 -stat- Lys12 ) is antibacterial polypeptide with high antibacterial activity, and DOPA provides strong adhesion in both wet and dry microenvironments. Meanwhile, compared to traditional "graft-onto" methods, this antibacterial coating can be facilely achieved by immersing Titanium substrates into antibacterial polypeptide solution for 5 min at room temperature. The poly(Phe10 -stat- Lys12 )-DOPA polymer showed good antibacterial activity with minimum inhibitory concentrations against S. aureus and E. coli of 32 and 400 μg/mL, respectively. Compared to obvious antimicrobial resistance of S. aureus after continuous treatment with vancomycin, this antibacterial coating doesn't drive antimicrobial resistance upon long-term utilization. Transcriptome sequencing and qPCR tests further confirmed that the antibacterial coating was able to inhibit the expression of multiple peptide resistance factor (mprF) and lipoteichoic acid modification D-alanylation genes (dltB and dltC) that can increase the net positive charge of bacterial cell wall to induce the resistance to cationic antimicrobial peptides. In vivo experiments confirmed that this poly(Phe10 -stat- Lys12 )-DOPA coating can both effectively prevent biofilm formation through surface contact sterilization and avoid local and systemic infections. Overall, we proposed a facile method for preparing antibacterial orthopedic implants with longer indwelling time and without inducing antimicrobial resistance by coating a polypeptide-based polymer on the implants. Graphical abstract: Image 1